"Ruthless Patience": A Conversation with Vikram Chandra. - Mukherjee, Oindrila (Gulf Coast: A Journal of Literature & Fine Arts)
Presents an interview with author Vikram Chandra. When asked about how he became a writer, Chandra discusses the influence of his mother who wrote for film, television, and radio in India and the benefits of graduate level creative writing programs. He also reflects on the process of writing fiction, the effect teaching has on his writing, and his use of Bombay, India in his fiction.